Evaluating the effects of Internal Control in the Operations of financial institutions: A Case Study of Bond Savings and Loans. - Adu-Frimpong, Afia Afra (2016)
A thesis submitted to the department of finance School of Business, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Business Administration (Finance).